A Comparative Study of Online Driver Language Learning in Indonesia and English in the Context of Tiktok Social Media - Helen Borland; Amirullah Abduh (Merwin Publisher, 2024)
This study aims to address problems encountered during EFL instruction by teachers and students. The problem identified in this study is the difficulty in learning English through a focused approach. The purpose of this study is to analyze the content of stand-up comedians' lessons in English and to determine whether these lessons can be applied to the routine of learning English for EFL students who view English as a part of their religion. The study will be conducted in a qualitative descriptive format, using observation and categorization methods to collect data from TikTok, a smartphone application that is well-known among students. This study will collect 50 videos from two TikTok accounts, one from Indonesian stand-up comedy and the other from English stand-up. The collected data will then be subjected to comparative analysis in order to determine the similarities and differences between comedians of the English language and English. The study's findings are significant in terms of using quality control techniques and teasing jokes to extract humor in both languages.